Tackling climate change: what is the impact on air pollution?. Issue 5 (October 2012) - Williams, Martin
This article addresses the impact of climate change policies on air pollution. It notes firstly that while the co-benefits of climate change to air pollution are potentially large, institutionally the links have yet to be made in a substantive way in international treaties and agreements. The article discusses economic studies that quantify and monetize the synergistic benefits to health and the environment arising from improved air quality in pursuit of climate change objectives. This article also discusses the areas where antagonisms might arise, necessitating trade-off decisions on the part of policymakers, notably in the use of biomass and diesel vehicles. It also discusses the merits of CCS for both climate change and air quality.